Analisis Fungsi Media Massa Dalam Channel Youtube “Loloan Project” - Ni Putu Yunita Anggreswari; Sheila Novita Isnaeni (Jayapangus Press, 2020)
Mass communication is a process of delivering messages / information to the general public. Communication is conveyed through a container that is the mass media. Mass media as a place to convey messages / information from the mass communication process has 4 (four) mass media functions, namely the information function, the educational function, the entertainment function, and the influence function. The four media functions will be linked to the YouTube channel by the local community of Loloan, the